1999
DOI: 10.1111/j.2042-3306.1999.tb05246.x
|View full text |Cite
|
Sign up to set email alerts
|

Standardisation of muscular biopsy ofgluteus mediusin French trotters

Abstract: Summary Morphometric measurements were taken from 41 French trotters of various ages and both sexes. Biopsy location was determined for the dorsal compartment as being one‐third of the distance from the tuber sacrale to the tuber coxae and for the ventral compartment as being one‐third of the distance from the tuber coxae to the caudal Cd1‐Cd2 intervertebral joint. Ten horses were biopsied at these 2 sites at a sampling depth equal to half the total depth of the compartment as measured by ultrasonography. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…The importance of exact standardisation of biopsying for depth, site and anatomical compartment of the equine gluteus muscle has been stressed previously (Bruce and Turek 1985;Kline et al 1 9 8 7 ;Wood et al 1988;Rivero et al 1992Rivero et al , 1993Bruce et al 1 9 9 3 ;Linnane et al 1999;Valette et al 1999). The results of the present study showed, additionally, that for samples only 3 cm apart laterally there were large differences between muscle variables, especially for the samples taken at 6 cm depth.…”
Section: Discussionsupporting
confidence: 60%
“…The importance of exact standardisation of biopsying for depth, site and anatomical compartment of the equine gluteus muscle has been stressed previously (Bruce and Turek 1985;Kline et al 1 9 8 7 ;Wood et al 1988;Rivero et al 1992Rivero et al , 1993Bruce et al 1 9 9 3 ;Linnane et al 1999;Valette et al 1999). The results of the present study showed, additionally, that for samples only 3 cm apart laterally there were large differences between muscle variables, especially for the samples taken at 6 cm depth.…”
Section: Discussionsupporting
confidence: 60%
“…All horses were sedated, and local anaesthesia was performed before making a small skin incision. The dorsal compartment of the gluteus medius biopsy was performed at the first third distance between the sacral and coxae tuber (Valette et al. 1999).…”
Section: Methodsmentioning
confidence: 99%
“…2008) or RER disease (Valberg et al . 1993) and (iii) the good standardisation of biopsy sampling (Valette et al . 1999).…”
Section: Methodsmentioning
confidence: 99%
“…For each horse, a microbiopsy of the gluteus medius muscle was performed under local anaesthesia. This muscle was chosen because of: (i) its important propulsion function in horse locomotion, (ii) its early and major histological involvement in the course of PSSM (Larcher et al 2008) or RER disease (Valberg et al 1993) and (iii) the good standardisation of biopsy sampling (Valette et al 1999). The horses were sedated and received a local anaesthesic before a small skin incision was made according to a standardised protocol used routinely for muscle disease diagnostis.…”
Section: Horses and Muscle Sample Collectionmentioning
confidence: 99%